Deep-learning based approach for forecast of water quality in intensive shrimp ponds - Lin, Qi; Yang, Wen; Zheng, Cheng; Lu, Kaihong; Zheng, Zhongming; Wang, Jianping; Zhu, Jinyong (Indian Journal of Fisheries, 2018)
With the enormous development of aquaculture, reducing the impacts of effluent discharge and improving water quality had become a critical global environmental concern. It is important to assess and predict water quality in the environmental management process of shrimp mariculture. Meanwhile, the accurate forecast of water quality is still in the exploration stage at present. In this study, deep belief networks (DBN) model are used to forecast water quality in intensive shrimp culture. This method based on deep learning includes a five-layered structure to extract relationships between the quantitative characteristic of water bodies and water quality variables. The water quality can be forecasted by the Canadian Water Quality Index (WQI) obtained from the output layer of simulated model. The results show that the DBN model has a great potential to predict the water quality and the ability of generalization and accuracy of model are satisfied.Â